New vanadium-based magnetic resonance imaging probes: clinical potential for early detection of cancer. - Mustafi, D; Peng, B; Foxley, S; Makinen, M; Karczmar, G; Zamora, M; Ejnik, J; Martin, H (2009)
We have developed a magnetic resonance imaging (MRI) method for improved detection of cancer with a new class of cancer-specific contrast agents, containing vanadyl (VO(2+))-chelated organic ligands, specifically bis(acetylacetonato)oxovanadium(IV) [VO(acac)(2)]. Vanadyl compounds have been found to accumulate within cells, where they interact with intracellular glycolytic enzymes. Aggressive cancers are metabolically active and highly glycolytic; an MRI contrast agent that enters cells with high glycolytic activity could provide high-resolution functional images of tumor boundaries and internal structure, which cannot be achieved by conventional contrast agents. The present work demonstrates properties of VO(acac)(2) that may give it excellent specificity for cancer detection. A high dose of VO(acac)(2) did not cause any acute or short-term adverse reactions in murine subjects. Calorimetry and spectrofluorometric methods demonstrate that VO(acac)(2) is a blood pool agent that binds to serum albumin with a dissociation constant K (d) ~ 2.5 +/- 0.7 x 10(-7) M and a binding stoichiometry n = 1.03 +/- 0.04. Owing to its prolonged blood half-life and selective leakage from hyperpermeable tumor vasculature, a low dose of VO(acac)(2) (0.15 mmol/kg) selectively enhanced in vivo magnetic resonance images of tumors, providing high-resolution images of their interior structure. The kinetics of uptake and washout are consistent with the hypothesis that VO(acac)(2) preferentially accumulates in cancer cells. Although VO(acac)(2) has a lower relaxivity than gadolinium-based MRI contrast agents, its specificity for highly glycolytic cells may lead to an innovative approach to cancer detection since it has the potential to produce MRI contrast agents that are nontoxic and highly sensitive to cancer metabolism.